Methods of regional innovative clusters forming and development programs elaboration - Marchuk, Olha (Видавництво Львівської політехніки, 2013)
The aim of the article is to select programmes for the formation and development of innovative cluster structures. The analysis of the backgrounds of formation of innovative clusters was made in the regions of Ukraine. Two types of programmes were suggested for the implamentation of cluster policy at the regional level.
Keywords: innovative clusters; forming; development; regional policy; regional programm